A robust vector tracking loop based on diagonal weighting matrix for navigation signal. Issue 12 (15th December 2017) - Lin, Honglei; Huang, Yangbo; Tang, Xiaomei; Sun, Guangfu; Ou, Gang
Abstract: VTL (Vector Tracking Loop) has a better tracking performance in sensitivity, dynamic, usability and reacquisition, but it is less robust due to its dependence of all channels and also may result in tracking deviation. To solve these problems, an RVTL (Robust Vector Tracking Loop) based on a diagonal weighting matrix is explored. In this method, a diagonal weighting matrix is used to replace the traditional weighting matrix in VTL. Analyses and simulations show that RVTL is more robust and keeps tracking results with no deviation, however, its tracking precision is a litter worse than VTL.